Direct evidence of causality between chemical purity and band-edge potential fluctuations in nanoparticle ink-based Cu2ZnSn(S, Se)4 solar cells. (31st January 2019) - Campbell, S; Qu, Y; Major, J D; Lagarde, D; Labbé, C; Maiello, P; Barrioz, V; Beattie, N S; Zoppi, G
Abstract: Kesterite solar cells based on chalcogenide Cu2 ZnSn(S, Se)4 (CZTSSe) are a viable approach to thin film photovoltaics, utilising Earth-abundant, non-toxic elements. CZTSSe films produced from nanoparticle inks offer a cost-effective solution-based method of fabrication. However, improving efficiency in these devices has proved challenging, in part due to the presence of detrimental complex defects within the bulk of the CZTSSe absorber. In this study, the behaviour of nanoparticle-based CZTSSe absorbers and solar cells made from relatively low and high quality grade chemicals is investigated with a view to improving cost-effectiveness of the ink-based fabrication process. Photoluminescence spectroscopy revealed the presence of similar shallow acceptor plus shallow donor states in both low and high purity precursor absorbers. We demonstrate a relationship between the average depth of energy band-edge potential fluctuations and absorber quality where the higher grade chemical precursor-based absorber outperforms the lower purity version. In addition, the low purity precursor absorber had a higher total defect density resulting in a 10 meV increase in the average electrostatic potential fluctuations. Deep level transient spectroscopy in solar devices indicated the presence of detrimental deep defect states in both types of absorber. Notwithstanding the high purity precursor absorber with lower defect density, the power conversion efficiencies of both types of CZTSSe solar cells were similar (̃5%), implying an issue other than defects in the absorber bulk inhibits device performance as evidenced by quantum efficiency analysis and current–voltage measurements.